The interconnection between cytokeratin and cell membrane-bound β-catenin in Sertoli cells derived from juvenile Xenopus tropicalis testes - Nguyen, Thi Minh Xuan; Vegrichtova, Marketa; Tlapakova, Tereza; Krulova, Magdalena; Krylov, Vladimir (Biology open, 2019)
Sertoli cells (SCs) play a central role in the determination of male sex during embryogenesis and spermatogenesis in adulthood. Failure in SC development is responsible for male sterility and testicular cancer. Before the onset of puberty, SCs are immature and differ considerably from mature cells in post-pubertal individuals regarding their morphology and biochemical activity. The major intermediate filament (IF) in mature SCs is vimentin, anchoring germ cells to the seminiferous epithelium. The collapse of vimentin has resulted in the disintegration of seminiferous epithelium and subsequent germ cell apoptosis. However, another IF, cytokeratin (CK) is observed only transiently in immature SCs in many species. Nevertheless, its function in SC differentiation is poorly understood. We examined the interconnection between CK and cell junctions using membrane β-catenin as a marker during testicular development in the Xenopus tropicalis model. Immunohistochemistry on juvenile (5 months old) testes revealed co-expression of CK, membrane β-catenin and E-cadherin. Adult (3-year-old males) samples confirmed only E-cadherin expression; CK and β-catenin were lost. To study the interconnection between CK and β-catenin-based cell junctions, the culture of immature SCs (here called XtiSCs) was employed. Suppression of CK by acrylamide in XtiSCs led to breakdown of membrane-bound β-catenin but not F-actin and β-tubulin or cell-adhesion proteins (focal adhesion kinase and integrin β1). In contrast to the obvious dependence of membrane β-catenin on CK stability, the detachment of β-catenin from the plasma membrane via uncoupling of cadherins by Ca2+ chelator EGTA had no effect on CK integrity. Interestingly, CHIR99021, a GSK3 inhibitor, also suppressed the CK network, resulting in the inhibition of XtiSCs cell-to-cell contacts and testicular development in juvenile frogs. This study suggests a novel role of CK in the retention of β-catenin-based junctions in immature SCs, and thus provides structural support for seminiferous tubule formation and germ cell development.
Keywords: Immature Sertoli cells; Xenopus tropicalis; Cytokeratin; Testicles; Adherens junctions